A novel interspecies recombinant enterovirus (Enterovirus A120) isolated from a case of acute flaccid paralysis in China. Issue 1 (1st January 2020) - Lu, Huanhuan; Hong, Mei; Zhang, Yong; Xiao, Jinbo; Zhang, Man; Zhang, Keyi; Song, Yang; Han, Zhenzhi; Yang, Qian; Wang, Dongyan; Yan, Dongmei; Zhu, Shuangli; et al.
ABSTRACT: EV-A120 is a recently identified serotype of the enterovirus A species. Only one full-length genomic sequence is currently available in GenBank, and very few studies have been conducted on EV-A120 globally. Thus, additional information and research on EV-A120 are needed to explore its genetic characteristics, phylogeny, and relationship with enteroviral disease. In this study, we report the phylogenetic characteristics of a EV-A120 strain ( Q0082 /XZ/CHN/2000) from Tibet, China. The amino acid sequence similarity and nucleotide sequence similarity of the full-length genomic sequence of this EV-A120 strain and the EV-A120 prototype strain were 96.3% and 79.9%, respectively, showing an evolutionary trend. Recombination analysis found intraspecies recombination in the 5′ -UTR, 2B, 2C, and 3D regions. Serum neutralization testing of the EV-A120 ( Q0082 ) strain was also carried out. Low serum-positive rates and geometric mean titres (GMTs) indicated that the extent of EV-A120 transmission and exposure in the population was very limited compared with that in the outbreaks of EV-A71 and CV-A16 in China since 2008. The EV-A120 strain ( Q0082 ) is non-temperature sensitive, indicating its potential to spread in the population. In summary, this study reports the full-length genomic sequence of EV-A120 and provides important information for its global molecular epidemiology.